Does Doing Good Diminish Cost of Capital? Evidence From South-East Asia Markets - Rizqi Umar, Al Hashfi (Journal of Accounting Inquiry, 2022)
Purpose: The ultimate goal of this study is to reassess the impact of ESG on the cost of capital. Methodology: This work is quantitative type using secondary data collected by Thomson & Reuters and World Bank. There are 247 sample companies in the 2009 – 2021 period spread across five Southeast Asian countries. The research uses the fixed effect method at the industrial level and the instrumental variable regression technique, which is estimated using the generalized moment (GMM) method to accommodate endogeneity. Findings: The ESG, ENVI, and SOCI coefficients are negative and statistically significant at the 1% level, further confirming that ESG performance is negatively associated with the cost of capital. Environmental and social aspects determine the level of the cost of capital. Meanwhile, governance issues are not a determining factor that can reduce the cost of capital. Novelty: Numerous studies have revealed inconclusive outcomes regarding the effectiveness of ESG in decreasing the cost of capital, particularly in Asian nations owing to their subpar institutional quality. This research seeks to bridge this gap by examining this relationship in the Southeast Asian countries. Keywords: Environment, Social, Governance, Cost of Capital, South-East Asia